"Can you speak German?" A theoretical review of the importance of intrinsic motivation for migrants in Germany to learn German (Journal of Advanced Research in Social Sciences, 2022)
Learning a new language is not simply memorizing grammar rules. It is a much deeper process of “being” in that speech. Identity and belonging can be strong motivators to learn and practice a new language, but they can be detrimental in certain cases. When perceiving discrimination as an immigrant, one might move away from the local language, as a reaction to feeling unwelcomed in that environment. A stronger connection to the identity as an “immigrant” may arise and, in some cases, it can even hinder language acquisition. In this article, we will explore the connections between perceiving xenophobic experiences as an immigrant and the impact it can have on the motivation to learn the local language.